2018
DOI: 10.1111/1745-9125.12199
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the dichotomy: Incarceration dosage and mental health*

Abstract: The findings from a growing body of research reveal that incarceration is detrimental for both physical and mental health. Incarceration, however, is typically conceptualized and operationalized as a dichotomy; individuals either have, or have not, been incarcerated. Considering that incarceration can range from one day to several years, a dichotomous measure may be overlooking important variations across lengths of exposure. In addition, most inmates are incarcerated more than once. In this study, we help to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 80 publications
(103 reference statements)
3
43
2
Order By: Relevance
“…Because Add Health does not differentiate jail from prison stays or provide detailed incarceration histories, a more nuanced understanding of how incarceration spells shape health is not possible, although this is an important area for future research inquiry. Taken together, the results presented here are consistent with the notion that incarceration history is not a "dichotomous" experience (Porter and DeMarco 2019), with individuals having varying durations and dosages of incarceration in ways that matter for health and warrant consideration.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Because Add Health does not differentiate jail from prison stays or provide detailed incarceration histories, a more nuanced understanding of how incarceration spells shape health is not possible, although this is an important area for future research inquiry. Taken together, the results presented here are consistent with the notion that incarceration history is not a "dichotomous" experience (Porter and DeMarco 2019), with individuals having varying durations and dosages of incarceration in ways that matter for health and warrant consideration.…”
Section: Discussionsupporting
confidence: 86%
“…It is possible that the first incarceration is a particularly salient stressor in the lives of individuals with especially grave consequences for health. After multiple incarcerations, individuals may "adapt" and be better equipped to handle the stress associated with incarceration (Porter and DeMarco 2019). It is also possible that those reporting higher incarceration dosage have experienced several jail-rather than prison-stays, which may relate to health in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is wide applicability of a health‐based model of desistance, we zero in on a population reentering society in which the impact of health on adult roles and recidivism comes into sharp focus. Indeed, individuals who have experienced incarceration are likely to suffer from poor health (Dumont, Brockmann, Dickman, Alexander, & Rich, ; Massoglia & Pridemore, ; Porter & DeMarco, ; Turney, Wildeman, & Schnittker, ; Wakefield & Uggen, ; Wildeman, ). Several study findings have demonstrated the deleterious impact of incarceration on morbidities related to infectious diseases and stress (Massoglia, ; Massoglia & Pridemore, ; Schnittker & John, ).…”
mentioning
confidence: 99%
“…Offenders may also have been less likely to appear in voter registration records and telephone directories, both of which were used to find respondents. The small number of convicted offenders precluded an analysis of the effect the number of convictions or incarceration; both factors may play a role in health outcomes among offenders and population-wide health disparities (Lee et al, 2014, Massoglia, 2008, Porter and DeMarco, 2018, Rosen et al, 2008, Schnittker et al, 2011, Wang et al, 2009, Wildeman, 2016, Wildeman and Wang, 2017). The small sample size also prevented further reliable exploration of genetic and environmental influence (Verhulst, 2017).…”
Section: Discussionmentioning
confidence: 99%